(untitled) (World Economics and Finance Bulletin, 2026)
The article examines the problems of harmonization of digital technologies with the principles of environmental sustainability in the financial market of Uzbekistan. The essence of the concept of green fintech, its application in international experience, and the possibilities of practical implementation in the conditions of Uzbekistan are studied. The importance of digital infrastructure in creating ecological financial solutions, mechanisms for supporting green investments, and the role of state policy are also underlined. The results of the research allow considering the green fintech system as an innovative factor in ensuring sustainable economic development and environmental safety in the country